Abdominal Visceral Adipose Tissue and All-Cause Mortality: A Systematic Review - Saad, Randa K.; Ghezzawi, Malak; Horanieh, Renee; Khamis, Assem M.; Saunders, Katherine H.; Batsis, John A.; Chakhtoura, Marlene (Frontiers in Endocrinology, 2022)
Introduction: Increased abdominal visceral adipose tissue (VAT) implies an adverse cardio-metabolic profile. We examined the association of abdominal VAT parameters and all-cause mortality risk. Methods: We systematically searched four databases. We performed citations/articles screening, data abstraction, and quality assessment in duplicate and independently (CRD42020205021). Results: We included 12 cohorts, the majority assessing VAT area (cm2), using computed tomography. Six cohorts, examining all-cause mortality risk per increment in VAT area (cm2) or volume (cm3), showed a 11-98% relative risk increase with higher VAT parameters in studies with a mean age ≤ 65 years. However, the association lost significance after adjusting for glycemic indices, body mass index, or other fat parameters. The findings were inconsistent in 4 cohorts on older populations. Conversely, in two cohorts (mean age 73-77 years), a higher VAT density, was inversely proportional to VAT area, and implied higher mortality risk. Conclusion: A high abdominal VAT area seems to be associated with increased all-cause mortality in individuals ≤ 65 years, possibly mediated by metabolic complications, and not through an independent effect. This relationship is weaker and may reverse in older individuals, most likely secondary to confounding bias and reverse causality. An individual participant data meta-analysis is needed to confirm our findings, and to define an abdominal VAT area cutoff implying increased mortality risk.